PENGARUH FAKTOR KEUANGAN DAN NON KEUANGAN PADA OPINI AUDIT GOING CONCERN - Yaqin, muhammad Ainun; Sari, Maria M. Ratna (E-Jurnal Akuntansi, 2015)
Opinion is useful to investors in providing investment, because if given opinion going concern then it becomes a negative signal about the continuity of the business of a company. Financial and non financial factors such as audit tenure, reputation of  public accounting firm, disclosure, liquidity,  the previous audit opinion is have a connection with audit opinion going concern in helping investors predict the survival of a company. This research aims to test the influence of audit tenure, reputation  of public accounting firm, disclosure, liquidity, and the previous  audit opinion against the audit opinion going concern at a manufacturing company listingson IDX in 2010-2013. Method determination of the sample using a purposive sampling techniques where appropriate criteria set retrieved 22 companies . Logistic regression analysis is using this research. . The results of this research suggests that the reputation of public accounting firm and the previous audit opinion influence significantly against audit opinion going concern, whereas tenure, disclosure and liquidity does not audit opinions affect the going concern.
Keywords: tenure, disclosure, liquidity, going concern